Reading through photography: Roland Barthes’s last seminar “Proust et la photographie” - Yacavone, Kathrin (University of Nebraska Press, 2009)
Focused on Roland Barthes’s notes for the last seminar of his Collège de France lecture series, entitled “Proust et la photographie,” this article considers the later Barthes’s conceptions of reading and writing, arguing that they are closely intertwined with his reflections on photography. Marcel Proust is cast as the paradigmatic author in Barthes’s post-1968 critical writing, in which he serves as both an exemplar for the complex process of transforming life into literature and as a figure of profound identification for Barthes the would-be novelist. À la recherche du temps perdu is a clear case of a literary work informed by its author’s life that at the same time denies or problematises straightforward autobiography. For Barthes the experience and study of Proust’s masterpiece entails a play with autobiographical ‘clefs’ that can be considered an activity on the part of Barthes’s pleasure-seeking reader, one that has significant theoretical implications regarding the apprehension of any literary text. As analysis of “Proust et la photographie” and La Chambre claire reveals, the photograph for Barthes signifies the oscillation between the imaginary and the real, fiction and (auto)biography, that characterises both literary authorship and readership.